2010
DOI: 10.1021/tx100045h
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Selective Modulator of Aryl Hydrocarbon (Ah) Receptor Activity that Exhibits Anti-Inflammatory Properties

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that mediates the toxicity of 2,3,7,8-tetrachlorodibenzo-p-dioxin. However, the role of the AHR in normal physiology is still an area of intense investigation. For example, this receptor plays an important role in certain immune responses. We have previously determined that the AHR can mediate repression of acute-phase genes in the liver. For this observation to be therapeutically useful, selective activation of the AHR would likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 44 publications
5
64
1
Order By: Relevance
“…TCDD was kindly provided by Dr. Stephen Safe (Texas A&M University, College Station, TX). 1-Allyl-3-(3,4-dimethoxyphenyl)-7-(trifluoromethyl)-1H-indazole (SGA360) was synthesized as described previously (Murray et al, 2010b). ␣NF and 6,2Ј,4Ј-trimethoxyflavone (TMF) were acquired from Indofine Chemicals (Hillsborough, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…TCDD was kindly provided by Dr. Stephen Safe (Texas A&M University, College Station, TX). 1-Allyl-3-(3,4-dimethoxyphenyl)-7-(trifluoromethyl)-1H-indazole (SGA360) was synthesized as described previously (Murray et al, 2010b). ␣NF and 6,2Ј,4Ј-trimethoxyflavone (TMF) were acquired from Indofine Chemicals (Hillsborough, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences of primers used for quantitative PCR have been described previously (Murray et al, 2010b). PerfeCTa SYBR Green SuperMix for iQ (Quanta Biosciences, Gaithersburg, MD) was used to determine mRNA levels, and analysis was conducted using MyIQ software, in conjunction with a MyIQ-single-color PCR detection system (Bio-Rad Laboratories, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AHR plays important roles in development and differentiation, as well as in the immune and the reproductive systems (1,2). Moreover, AHR has recently emerged as a therapeutic target for inflammatory and autoimmune diseases, as well as for the treatment of breast cancer (3,4). We and others have shown that AHR activation inhibits estrogen receptor-a (ERa) signaling through direct interaction with ERa and through the modulation of ERa target genes (5-7).…”
Section: Introductionmentioning
confidence: 99%